2022
DOI: 10.3390/antib11010015
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of PD-L1 versus PD-1 Expression in Circulating CD20 Cells in Diffuse Large B-Cell Lymphoma

Abstract: This study aimed to investigate PD-L1 and PD-1 expression in circulating CD20+ cells in diffuse larger B-cell lymphoma (DLBCL) and to evaluate the predictive and diagnostic performance of PD-L1 versus PD-1 expression in circulating CD20+ cells in DLBCL. Percentages of CD20+, PD-L1+CD20+, and PD-1+CD20+ cells were measured by flow cytometry in 40 DLBCL blood samples and 19 healthy controls. The DLBCL patient group was subdivided into 20 newly diagnosed patients with no treatment yet and 20 patients that had fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
3
1
0
Order By: Relevance
“…Consistently, the biomarkers maintained high AUC values in this validation cohort, further substantiating the robustness of the model and its potential to be generalized across previously unseen data. These observations were consistent with those of previous studies [48][49][50] . www.nature.com/scientificreports/ MAPK8 showed high connectivity in the PPI networks.…”
Section: Discussionsupporting
confidence: 94%
“…Consistently, the biomarkers maintained high AUC values in this validation cohort, further substantiating the robustness of the model and its potential to be generalized across previously unseen data. These observations were consistent with those of previous studies [48][49][50] . www.nature.com/scientificreports/ MAPK8 showed high connectivity in the PPI networks.…”
Section: Discussionsupporting
confidence: 94%
“…The results indicated that NHL patients had immune-function deficiencies in their peripheral blood, suggesting an immune defect. In agreement with previous reports, the study revealed that NHL patients had significantly decreased peripheral immune-cell percentages compared with the healthy controls [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ]. When the immune system cannot function optimally, T and B cells fail to detect or destroy tumor cells [ 18 , 34 ].…”
Section: Discussionsupporting
confidence: 92%
“…The findings revealed that immune evasion could be mediated by mechanisms other than tumoral PD-L1 expression. The NHL patients had a significantly greater PD-L1 upregulation in circulating lymphocytes than the healthy controls; this was consistent with a previous study [ 32 ]. The mechanisms behind the PD-L1 increase in circulating immune cells are unknown.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation